2012
DOI: 10.1097/coc.0b013e318210f54a
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoprogression in Patients With Glioblastoma Multiforme After Concurrent Radiotherapy and Temozolomide

Abstract: Current results indicates the urgency of need for novel imaging techniques and/or biochemical marker(s) that can better distinguish pseudoprogression from true progression to avoid unnecessary and potentially harmful surgical interventions in almost half of the radiologically progressive GBM patients. Our additional observation which suggests better survival for patients with pseudoprogression warrants to be studied in larger patient cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 22 publications
1
52
0
Order By: Relevance
“…The surgery for suspected recurrence occurred at a median of 9.3 months after the initial diagnosis. The median survival from surgery for suspected recurrence and from initial diagnosis was 8 [514] and 20 [1230] months, respectively. Following pathological review, 17 patients (29, 95 % CI 18–42 %) had a diagnosis of “no active high-grade tumor”.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The surgery for suspected recurrence occurred at a median of 9.3 months after the initial diagnosis. The median survival from surgery for suspected recurrence and from initial diagnosis was 8 [514] and 20 [1230] months, respectively. Following pathological review, 17 patients (29, 95 % CI 18–42 %) had a diagnosis of “no active high-grade tumor”.…”
Section: Resultsmentioning
confidence: 99%
“…tumor progression that had received standard chemo-radiation therapy, who were re-operated for histopathological confirmation. They found that 19 % of these patients had pseudoprogression and that this pathologic diagnosis corresponded with improved survival using non-controlled, log-rank analysis [12]. The authors mention morphologic characterization, however they did not offer clear histopathological criteria for the diagnosis of pseudoprogression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 However, the appearance of enhancing lesions on MR imaging within the first 6 months after completion of chemoradiation therapy poses a challenge because it can reflect true progression (TP) or treatment-related changes known as pseudoprogression (PsP). PsP occurs in approximately a third of all patients with glioblastoma, 3 in which lesions often decrease in size or stabilize without further treatment, resulting in a longer survival. Accurate identifica-tion of PsP and TP is critical because patients with TP may require a change in therapeutic strategy while those with PsP may not.…”
mentioning
confidence: 99%